Long-term pegylated interferon-α and its potential in the treatment of melanoma - Reinhard Dummer (Dove Medical Press, 2009)
Reinhard Dummer, Joanna ManganaDepartment of Dermatology, University Hospital, Zürich, SwitzerlandAbstract: Conventional interferons including interferon-α (IFN-α) are cytokines used for years in the treatment of solid tumors and hematological malignancies. Their half-life is short. Pegylated forms of IFN-α present an improved pharmacokinetic profile that rendered them the preferred IFNs in hepatitis therapy. In the last decade, pegylated interferons (PegIFNs) have been investigated in melanoma patients. We review the scientific published literature on biology, pharmacokinetics, side effects and clinical applications of PegIFN-α in the treatment of stage III and IV melanoma. In the adjuvant setting, PegIFNα-2b has significant prolonged distant metastases free survival in patients with microscopic nodal involvement (stage TxN1aM0) and therefore is a promising treatment option in this patient population. In the palliative setting, monotherapy with PegIFNα-2α can induce complete remissions in a minority of stage IV melanoma patients. The combination of monochemotherapy is feasible and may result in lasting complete remissions. Ongoing research must focus on the identification of patients who mostly benefit, so that unnecessary toxicity would be avoided. Combining PegIFNs and chemotherapy or targeted agents deserves further exploration.Keywords: interferons, pegylated interferon-α, melanoma